Delays in Time-To-Antibiotics for Young Febrile Infants With Serious Bacterial Infections: A Prospective Single-Center Study - Yang, Jinghui; Ong, Wei Jie; Piragasam, Rupini; Allen, John Carson; Lee, Jan Hau; Chong, Shu-Ling (Frontiers in Pediatrics, 2022)
Introduction: Fear of missed serious bacterial infections (SBIs) results in many febrile young infants receiving antibiotics. We aimed to compare the time to antibiotics between infants with SBIs and those without. Materials and Methods: We recruited febrile infants ≤90 days old seen in the emergency department (ED) between December 2017 and April 2021. SBI was defined as (1) urinary tract infection, (2) bacteremia or (3) bacterial meningitis. We compared the total time (median with interquartile range, IQR) from ED arrival to infusion of antibiotics, divided into (i) time from triage to decision for antibiotics and (ii) time from decision for antibiotics to administration of antibiotics. Results: We analyzed 81 and 266 infants with and without SBIs. Median age of those with and without SBIs were 44 (IQR 19-72) and 29 (IQR 7-56) days, respectively (p=0.002). All infants with SBIs and 168/266 (63.2%) infants without SBIs received antibiotics. Among 249 infants who received antibiotics, the median total time from ED arrival to infusion of antibiotics was 277.0 (IQR 236.0-385.0) mins for infants with SBIs and 304.5 (IQR 238.5-404.0) mins for those without (p=0.561). The median time to decision for antibiotics was 156.0 (IQR 115.0-255.0) mins and 144.0 (IQR 105.5-211.0) mins, respectively (p=0.175). Following decision for antibiotics, infants with SBIs received antibiotics much faster compared to those without [107.0 (IQR 83.0-168.0) vs 141.0 (94.0-209.5) mins, p=0.017]. Conclusion: There was no difference in total time taken to antibiotics between infants with SBIs and without SBIs. Both recognition and administration delays were observed. While all infants with SBIs were adequately treated, more than half of the infants without SBIs received unnecessary antibiotics. This highlights the challenge in managing young febrile infants at initial presentation, and demonstrates the need to examine various aspects of care to improve the overall timeliness to antibiotics.